2016
DOI: 10.1038/srep27589
|View full text |Cite|
|
Sign up to set email alerts
|

MC1R is dispensable for the proteinuria reducing and glomerular protective effect of melanocortin therapy

Abstract: Melanocortin therapy by using adrenocorticotropic hormone (ACTH) or non-steroidogenic melanocortin peptides attenuates proteinuria and glomerular injury in experimental glomerular diseases and induces remission of nephrotic syndrome in patients with diverse glomerulopathies, even those resistant to steroids. The underlying mechanism remains elusive, but the role of melanocortin 1 receptor (MC1R) has been implicated and was examined here. Four patients with congenital red hair color and nephrotic syndrome cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 75 publications
(118 reference statements)
1
13
0
Order By: Relevance
“…6 ). This could explain how patients with nephrotic syndrome carrying MC1R mutations impairing cAMP response can benefit from ACTH treatment 23 , by still having intact ERK1/2 signaling downstream of the MC1R.…”
Section: Discussionmentioning
confidence: 99%
“…6 ). This could explain how patients with nephrotic syndrome carrying MC1R mutations impairing cAMP response can benefit from ACTH treatment 23 , by still having intact ERK1/2 signaling downstream of the MC1R.…”
Section: Discussionmentioning
confidence: 99%
“…10,17 A number of studies suggest that the beneficial effect of melanocortin therapy is likely due to a direct action on podocytes. 10,18 Podocytes are a critical component of the glomerular filtration barrier controlling glomerular permeability, and podocytopathy is thought to underlie the massive proteinuria observed in diverse glomerular diseases. Melanocortin receptors are expressed in glomerular podocytes and it has been shown that receptor stimulation can reduce oxidative stress and improve glomerular morphology by diminishing podocyte apoptosis, injury, and loss in the remnant kidney animal model.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Qiao et al 44 found a nonsteroidogenic melanocortin pan agonist to be equally effective in reducing proteinuria and ameliorating podocyte ultrastructural changes in MC1R -mutant and wild-type mice exposed to lipopolysaccharide or adriamycin. They also reported complete remissions with ACTH in two patients with mutated MC1R (congenital red hair) and refractory MN.…”
Section: Discussionmentioning
confidence: 89%
“…They also reported complete remissions with ACTH in two patients with mutated MC1R (congenital red hair) and refractory MN. 44 In a mouse model of experimental FSGS (adriamycin nephrosis), neither a MC1R agonist nor α-MSH had any beneficial effect on proteinuria or morphology. 43 In comparison, a significant beneficial effect of Acthar Gel was found in a model of secondary FSGS (nephron reduction), 45 even though corticosteroids are known to exacerbate injury in this model.…”
Section: Discussionmentioning
confidence: 97%